2003
DOI: 10.1210/jc.2003-030586
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Loss of Thyroglobulin Iodination and the Expression of Thyroid-Specific Proteins Involved in Iodine Metabolism in Thyroid Carcinomas

Abstract: Progress in biotechnology has provided useful tools for tracing proteins involved in thyroid hormone synthesis in vivo. Mono- or polyclonal antibodies are now available to detect on histological sections the Na(+)/I(-) symporter (NIS) at the basolateral pole of the cell, the putative iodide channel (pendrin) at the apical plasma membrane, thyroperoxidase (TPO), and members of the NADPH-oxidase family, thyroid oxidase 1 and 2 (ThOXs), part of the H(2)O(2)-generating system. The aim of this study was to correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 34 publications
8
52
0
1
Order By: Relevance
“…In both RET/PTC3 and E7 transgenic mouse thyroids, the ability to concentrate radioiodide is generally reduced as in human thyroid carcinomas (Gérard et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both RET/PTC3 and E7 transgenic mouse thyroids, the ability to concentrate radioiodide is generally reduced as in human thyroid carcinomas (Gérard et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This can be correlated with data in the human PTC. It could be due to an increased intracellular NIS misexpression (Saito et al, 1998;Wapnir et al, 2003;Riesco-Eizaguirre and Santisteban, 2006), to conformational changes (Gérard et al, 2003) or to the non maturation of hNIS (Trouttet-Masson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown predominantly intracellular localization of NIS protein in thyroid tumors (30)(31)(32).…”
Section: Discussionmentioning
confidence: 83%
“…Several studies have found that TSHR expression closely parallels other markers of differentiation, such as thyroglobulin and thyroperoxidase (Hoang-Vu et al 1992, Elisei et al 1994, Park et al 2000. However, evidence from a number of studies of resected thyroid tissue suggests that TSHR is more persistently expressed than other differentiation markers, including NIS and thyroglobulin proteins , Lazar et al 1999, Gerard et al 2003, indicating not only that TSHR may remain an important signaling pathway for cellular growth but also its utility as a conserved therapeutic target. Further in vivo evidence of continued TSHR expression in the absence of NIS is provided by a study of 63 patients with metastatic DTC, and no radioactive iodine uptake on whole body scan, who underwent 18 F-fludeoxyglucose positron emission tomography ( 18 F-FDG-PET) both under basal conditions and after rhTSH stimulation (Leboulleux et al 2009).…”
Section: Persistence Of Tshr Expression In the Setting Of Loss Of Othmentioning
confidence: 99%